KARAKTERISASI ENZIM PROTEASE DARI AMYLOMYCES ROUXII B - , DWI SETYO PAMUNGKAS, Dr. Ir. Retno Indrati , M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Rennet is a proteolytic enzyme that used as a coagulant in the cheesemaking process. Rennet is obtained from the abomasum were still breast-feeding mammals and genetically modified microbes. However, the use of rennet as a coagulant limited to production, religion, diet, and public awareness of food processed from genetically modified microbes. Much research has been done to find an alternative rennet, one of which is a protease from the plant. Natural coagulants have been identified from plants found in bromelin, papain and ficin . However, protease from the plant causes a bitter taste in the cheese so it cannot be used as a coagulant protein. Therefore, they needed another protease alternatives, one of which is Amylomyces rouxii are often used in local fermented of tape ketan. To determine the proteolytic activity of Amylomyces rouxii, first, qualitative test using agar skim ( agar 1.5 % and skim 2 % ) . Characteristics of the enzyme begins by test the optimum incubation time with the variation of time ( 0 , 20 , 40 , 60 , 80 , 100 , 120 and 140 minutes ) and CaCl2 concentration. Effect of substrate temperature and pH were measured at several levels of temperature (room temperature , 300, 350, 400, 450, and 500C ) as well as variations in pH (5, 5.5 , 6 , 6.5 , 7 , 7.5 and 8 ) . The effect of adding a metal ion salts ( CaCl2, MgCl2 , ZnCl2 , FeCl2 and CuCl2 ) were tested to determine its effect in curding. Results indicate that the protease of Amylomyces rouxii has optimum activity at pH 5 and temperature of 400C . The optimum incubation time at 60 minutes incubation and the concentration of CaCl2 to be added is 0.15 % (w /v) . Some metal ions affect the activity of the enzyme . During storage at 40C, protease activity decreased with a half-life ( T50 ) 5.04 days. Crude enzymes from Amylomyces rouxii can coagulate milk protein solids with recovery 58.25 % .